2012
DOI: 10.1016/j.juro.2012.04.097
|View full text |Cite
|
Sign up to set email alerts
|

Fragility of Brushite Stones in Shock Wave Lithotripsy: Absence of Correlation with Computerized Tomography Visible Structure

Abstract: Purpose Brushite stones were imaged in vitro and then broken with shock wave (SW) lithotripsy (SWL) to assess whether stone fragility correlates with internal stone structure visible by helical computed tomography (helical CT). Materials and Methods 52 brushite stones were scanned by micro CT, weighed, hydrated, and placed within a radiological phantom. The stones were scanned using a Philips Brilliance iCT 256 system, and the images evaluated for visibility of internal structural features. The stones were t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
7
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 19 publications
1
7
0
Order By: Relevance
“…Such structural characterization on pathological calcifications can be performed either through various classical physical techniques (Evan et al, 2007;Rao et al, 2011;Bazin et al, 2006), such as scanning electron microscopy (SEM) (Grà cia-Garcia et al, 2011;Dessombz, Mé ria et al, 2011, micro-computerized tomography (Williams et al, 2012;Kaiser et al, 2011), Fourier transform infrared (FTIR) and Raman spectroscopy (Quy Dao & Daudon, 1997;Estepa & Daudon, 1998;Guerra-Lopez et al, 2008;Wilson et al, 2010), proton induced X-ray emission (Pineda-Vargas et al, 2009), and laser ablation methods (Stepankova et al, 2013), or through techniques specific to large instruments, such as micro X-ray fluorescence (Bazin et al, 2007), micro X-ray absorption spectroscopy Carpentier et al, 2010;Nguyen et al, 2011), micro FTIR spectroscopy or neutron scattering (Bazin, André et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Such structural characterization on pathological calcifications can be performed either through various classical physical techniques (Evan et al, 2007;Rao et al, 2011;Bazin et al, 2006), such as scanning electron microscopy (SEM) (Grà cia-Garcia et al, 2011;Dessombz, Mé ria et al, 2011, micro-computerized tomography (Williams et al, 2012;Kaiser et al, 2011), Fourier transform infrared (FTIR) and Raman spectroscopy (Quy Dao & Daudon, 1997;Estepa & Daudon, 1998;Guerra-Lopez et al, 2008;Wilson et al, 2010), proton induced X-ray emission (Pineda-Vargas et al, 2009), and laser ablation methods (Stepankova et al, 2013), or through techniques specific to large instruments, such as micro X-ray fluorescence (Bazin et al, 2007), micro X-ray absorption spectroscopy Carpentier et al, 2010;Nguyen et al, 2011), micro FTIR spectroscopy or neutron scattering (Bazin, André et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…6,7 In this issue of The Journal Williams et al (page 996) built on this important work, now addressing the question of whether brushite stones demonstrate the same correlation between CT visible stone structure and stone fragility. 8 In contradistinction to what this investigative group found with cystine and calcium oxalate monohydrate stones, the internal structure of brushite stones did not help identify stones that would fragment more or less readily.…”
Section: The Need For Better Decision Tools In Managing Stone Diseasementioning
confidence: 87%
“…A previous study examining stone fragility based on stone composition concluded that knowing the composition alone may not accurately predict the fragility (13). However, other studies examining homogeneity (14), surface roughness (15), and internal stone structures visible with CT (16,17) have demonstrated that internal and external stone morphological features show correlation with kidney stone fragility. A recent study was demonstrated that quantitative relationships exist between stone fragility and stone morphological features extracted from routine singleenergy CT (SECT) and dual-energy CT (DECT) scans (12).…”
Section: Introductionmentioning
confidence: 99%